2001
DOI: 10.1161/01.cir.103.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Cardiac Denervation on Heart Rate Variability During Sleep

Abstract: Background-Cardiac vagal predominance increases the RR interval and RR high-frequency (HF) variability during non-rapid eye movement (non-REM) sleep (stages I through IV) in young subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
38
1
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 36 publications
9
38
1
3
Order By: Relevance
“…The HR during the central 6 h of sleep in both conditions was significantly lower in the young than in the middle-aged group. These data agree with the study of Crasset et al (23), which documented that the R-R interval did not differ between young and older subjects during awake periods but was higher in the young than in the older subjects during both rapid eye movement (REM) and non-REM sleep. Goldsmith et al (24) have also reported higher R-R interval values during the night in young men as an expression of vagal predominance during sleep.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The HR during the central 6 h of sleep in both conditions was significantly lower in the young than in the middle-aged group. These data agree with the study of Crasset et al (23), which documented that the R-R interval did not differ between young and older subjects during awake periods but was higher in the young than in the older subjects during both rapid eye movement (REM) and non-REM sleep. Goldsmith et al (24) have also reported higher R-R interval values during the night in young men as an expression of vagal predominance during sleep.…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, the established criterion was to analyze intervals with the highest stationary periods of ECG recording during sleep since this condition most likely occurs in the non-REM stages -when there is a shift of cardiac sympathovagal balance, with a corresponding increase in parasympathetic over sympathetic stimulation in the sinus node (23,26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies agree that age is inversely associated with RRV (Crasset et al, 2001;Gregoire et al, 1996;Kuo et al, 1999;Tsuji et al, 1996b;Yeragani et al, 1997). The data are less consistent on the impact of sex and race.…”
Section: Introductionmentioning
confidence: 94%
“…In human cardiovascular responses to adrenaline, α-adrenergic effects are predominant in female, whereas β-adrenergic effects are predominant in male [7]. Cardiac functions are declined with advancing ageing [8,9]. The decline might be in partial due to age-dependent alterations of the element contents, accompanied with gender differences.…”
Section: Introductionmentioning
confidence: 99%